Perancangan Sistem Informasi Inventory Pada Pt Jnb Global Menggunakan Php Dan My Sql - M Fatchan; Windi Tri Wahyuni (Teknik Informatika, Universitas Pelita Bangsa, 2018)
JNB GLOBAL was established in 2001 engaged in the supply of automotive spare parts. At present the system that runs still has many shortcomings and weaknesses causing the company's performance to be hampered such as making a report long enough so that the management waited a long time to get the results of the report. This study aims to calculate the incoming and outgoing goods available and can print transaction reports at PT JNB GLOBAL. Data collection techniques used are observation techniques. The design method will be described in the form of Use case diagrams, activity diagrams, sequence diagrams. Making this inventory information system uses the PHP programming language using MySQL as its database. Testing in this study was conducted using Black Box Testing. With the existence of an inventory system, it is hoped that it can help the company burden in processing inventory data and in making reports within the company